West Indian Fruit Fly, Anastrepha obliqua (Macquart) (Insecta: Diptera: Tephritidae) - Howard V. Weems; John B. Heppner; Gary J. Steck; Thomas R. Fasulo (EDIS)
Anastrepha obliqua is a major pest of mangoes in most tropical countries, making the production of some varieties unprofitable. In the United States, it is found in the Rio Grande Valley of Texas and was once found in Florida. It is intercepted frequently in mangoes and several other fruits from various countries. This revised 5-page fact sheet was written by H. V. Weems, Jr., J. B. Heppner, G. J. Steck, and T. R. Fasulo, and published by the UF Department of Entomology and Nematology, June 2012.